Strengthening Malaysian higher education: a contemporary discourse - Anuarudin, Aini Andria Shirin (UiTM Press, 2022)
Malaysia's higher education ecosystem has gone through impressive expansion and transformation during the COVID-19 pandemic. This book collates the efforts done and accomplishments received by Malaysia's higher education institutions and agencies. The book highlights the path towards maintaining excellence in a challenging new world.